Civil–Military Coordination: A Framework for Measuring Effectiveness in Humanitarian Response - Vincenzo Bollettino; Birthe Anders (Journal of Humanitarian Affairs, 2020)
In most of today’s crises, humanitarian organisations operate in the same environment as a range of military and non-state armed actors. The effective engagement between militaries and humanitarian aid agencies can be beneficial for the timely delivery of aid and is also often unavoidable when trying to gain access to areas controlled by military or non-state armed actors. However, such engagement also comes with risks. Previous literature on the subject has described some of the benefits and potential risks of different types of engagement between military and humanitarian actors. To date, however, quantifiable data on how civil–military engagement unfolds and which factors influence the effectiveness of coordination is lacking. This paper proposes an indicator framework for measuring the effectiveness of civil–military coordination in humanitarian response. It provides nineteen descriptive level and twenty perception and effectiveness indicators that may be used at any stage of a response to a humanitarian emergency, from mission planning and assessment through the various stages of a response and post-response assessment. The full set of questions, or a more targeted subset of these questions, may also be used as periodic polls to actively monitor developments in theatre.